2007
DOI: 10.1002/pon.1204
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physical and psychosocial factors on work characteristics after cancer

Abstract: Most previously employed cancer survivors continue to work after treatment, but the impact of cancer symptoms or psychosocial concerns on their work has seldom been assessed. We conducted a community-based survey of cancer survivors from the Colorado Central Cancer Registry to assess the changes in their work and the demographic, clinical, and psychosocial characteristics associated with work changes over the 2 years following diagnosis. Of 100 survivors, 92 returned to work, but 57% of those reduced their wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 30 publications
6
95
1
7
Order By: Relevance
“…Consistent with the literature, the perceived employer accommodation indicated a fairly positive attitude towards employment, work-related support, and necessary job changes (14,27,49) and emerged as a significant predictor for RTW.…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with the literature, the perceived employer accommodation indicated a fairly positive attitude towards employment, work-related support, and necessary job changes (14,27,49) and emerged as a significant predictor for RTW.…”
Section: Discussionsupporting
confidence: 69%
“…2,8 In addition, there are several factors that may influence cancer incidence, survival, and earnings. 19 In a statistical model for earnings, these should ideally be included as control variables, along with an indicator of the cancer illness.…”
Section: Methodsmentioning
confidence: 99%
“…6 Labor earnings may thus be affected by whether people encounter serious illnesses such as cancer, and perhaps also suffer from adverse treatment related side effects. [6][7][8][9] In addition, healthy spouses may need to spend time on caregiving tasks and thus reduce their own working hours or take on less challenging and less economically rewarding jobs. However, it is also possible that spouses work hard to earn higher incomes, to compensate for losses in partners' earnings.…”
mentioning
confidence: 99%
“…These late and longterm effects appear related to cancer survivors' own perceptions of their work ability as well as tangible outcomes such as work retention. In one study of 100 American heterogeneous cancer survivors, reducing work hours was associated with experiencing more physical symptoms including lack of energy and more psychological symptoms including feeling anxious or depressed, although the direction of this relationship is unknown (Steiner, et al, 2008). Fatigue and cognitive functioning are also among the factors that impact on the cancer survivor's selfperceived work ability and are related to time to return to work after the first day of sick leave (de Boer, et al, 2008).…”
Section: Late Effects Of Cancer and Their Relationship With Work Abilitymentioning
confidence: 99%
“…heterogeneous survivors two years after diagnosis, 57% of cancer survivors who were working reduced work by more than 4 hours/week, with a mean reduction of 15 hours/week (Steiner, et al, 2008). Of these survivors, 81% reported that the reduction was due to cancer.…”
Section: List Of Tables and Figuresmentioning
confidence: 99%